RISK FACTORS STRATIFICATION IN 100 PATIENTS WITH DIABETIC FOOT - Haider, Iqbal; Wahab, Fazal; Rashid, Ahmar; Hussain, Shakir; Bashir, Hamid (Journal of Postgraduate Medical Institute, 2011)
Objective: To find out the relative frequencies of various risk factors associated with Diabetic foot.